In Vitro and In Vivo Characterizations of Chiglitazar, a Newly Identified PPAR Pan-Agonist - B. K. He; Z. Q. Ning; Z. B. Li; S. Shan; D. S. Pan; B. C. B. Ko; P. P. Li; Z. F. Shen; G. F. Dou; B. L. Zhang; X. P. Lu; Y. Gao (PPAR Research)
Solid rationales are still present for the identification of synthetic ligands to simultaneously target multiple PPAR subtypes for the treatment of T2DM. The purpose of this study was to characterize the in vitro and in vivo differential effects of chiglitazar, a non-TZD type of PPAR pan-agonist currently in phase III clinic development in China, from PPARγ-selective agonist like rosiglitazone. Chiglitazar showed transactivating activity in each PPARα, γ, and δ subtype and upregulated the expression of PPARα and/or PPARδ downstream genes involved in the key processes of lipid metabolism and thermogenesis. Comparable blood glucose lowering effect was observed between chiglitazar and rosiglitazone, but chiglitazar did not significantly increase the body weight in KKAy and fat pad weight in db/db mice. Chiglitazar had high distribution in liver, pancreas, and skeleton muscles but was less present in kidney, heart, and adipose in rats. Heart weight increase was not observed in rats treated with chiglitazar for 6 months at a dose as high as 45 mg kg−1. The in vitro and in vivo differential features of chiglitazar are informative and encouraging for the further development of this synthetic ligand for the potential use in T2DM.